Faktor – Faktor Yang Mempengaruhi Persepsi Terhadap Kepatuhan Wajib Pajak - Herlina, Herlina; Putra, Rio Johan (Owner : Riset dan Jurnal Akuntansi, 2024)
This research aims to examine the influence of various factors, including perceptions of tax corruption, perceptions of justice, social influences and norms, legal and ethical awareness, as well as education and knowledge, on taxpayer compliance. The sample in this research was "taxpayers" in DKI Central Jakarta who were required to pay taxes in Indonesia, totaling 55 respondents. The sampling technique in this research used saturated samples. The data collection method uses a questionnaire. Data uses path coefficient analysis with the help of the Smart PLS program. The research results show the following: 1) Perceptions of tax corruption have no effect on taxpayer compliance. 2) Perceptions of fairness have a positive effect on taxpayer compliance. 3) Social influence and norms have no effect on taxpayer compliance. 4) Legal and ethical awareness has no effect on taxpayer compliance. 5) The level of education and knowledge has a positive effect on taxpayer compliance. In addition, education and knowledge play a moderating role in several relationships, such as: 1) Education and knowledge moderate the relationship between perceptions of tax corruption and taxpayer compliance. 2) Education and knowledge do not moderate the relationship between perceptions of fairness and taxpayer compliance. 3) Education and knowledge moderate the relationship between social influence and norms and taxpayer compliance. 4) Education and knowledge moderate the relationship between legal and ethical awareness and taxpayer compliance. In conclusion, higher levels of education and knowledge tend to increase taxpayer compliance, while the moderating role of education and knowledge can influence the relationship between several other factors and taxpayer compliance.